Biologics in severe asthma: Outcomes in clinical trials-Similarities and differences. (3rd July 2022) - Bakakos, Agamemnon; Rovina, Nikoletta; Loukides, Stelios; Bakakos, Petros
ABSTRACT: Introduction: Severe asthma is a heterogenous disease characterized by multiple phenotypes. Targeted biologic therapies have revolutionarily changed the management of severe asthma by affecting various clinical outcomes, mainly by reducing exacerbations and the use of maintenance corticosteroids, but also by improving lung function and patient quality of life. Areas covered: Randomized controlled trials have convincingly demonstrated the efficacy of different biologics in improving the above outcomes. However, no head-to-head studies exist to compare their efficacy and many patients with severe asthma are eligible for more than one biologic agent. In this review, we present the effect of various biologics in the various outcomes as shown in randomized controlled trials and discuss their similarities and differences. Expert opinion: Both the initial choice of a biologic as well as the option of switching to another give the clinician an interesting but also difficult decision when choosing a biologic therapy for patients with severe asthma. This decision is mainly based on the individual characteristics of the patient, especially rate of exacerbations and use of systemic corticosteroids, but is also influenced by the presence of comorbidities and lung function impairment. No safety concerns have been raised around the use of these biologics.